Mutation Spectrum of β-Thalassemia and Other Hemoglobinopathies in Chittagong, Southeast Bangladesh. (2nd November 2015) - Chatterjee, Tridip; Chakravarty, Amit; Chakravarty, Sudipa; Chowdhury, Mahmood Ahmed; Sultana, Razia
Abstract: Thalassemia is one of the most common autosomal recessive blood disorders in the world. It shows a variety of clinical expression, starting from asymptomatic to severe blood transfusion dependence. More than 500 alleles have been characterized in or around the β-globin region. Moreover, most geographical regions have their own characteristics, frequency and availability of these alleles, predominantly circulating within the communities present in that particular region. In this study, we explored the spectrum of β-thalassemia (β-thal) alleles present in Chittagong, Southeast Bangladesh. This study comprises β-thal and Hb E ( HBB : c.79 G > A) patients from in and around the area of Chittagong. Not only exploring the complete β-globin mutation spectrum of the area, but we also tried to look at the origin of the mutated alleles. The β-thal mutations of Bangladesh show a relatively wide spectrum of alleles, which further demonstrates the heterogeneity of the disease in this country. Although our study showed that the majority of the mutations have their origin in neighboring countries such as India, countries of Southeast Asia, Pakistan, etc., some unusual alleles do not originate in neighboring countries and put a little more diversity in the overall spectrum of β-thal-specific alleles. Overall, this study demonstrates the mutation spectrum related to β-thal in Chittagong, Southeast Bangladesh.